2016
DOI: 10.1016/j.jaci.2016.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the etiology of atopic disorders by using genetic analysis of racial ancestry

Abstract: Atopic dermatitis (AD), food allergy (FA), allergic rhinitis (AR) and asthma are common atopic disorders of complex etiology. The frequently observed “atopic march” from early AD to asthma and/or AR later in life as well as the extensive comorbidity of atopic disorders, suggests common causal mechanisms in addition to distinct ones. Indeed, both disease-specific and shared genomic regions exist for atopic disorders. Their prevalence also varies among races; for example, AD and asthma have a higher prevalence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 307 publications
(307 reference statements)
1
38
1
4
Order By: Relevance
“…It has been well‐demonstrated that filaggrin mutations are population specific, and that common filaggrin mutations in patients with severe AD of European descent are absent in patients of African descent. The fact that ethnic minorities often have a lower socio‐economic status and are more often associated with poor environmental conditions may also have a direct effect on the development of atopic disorders, and this needs to be carefully adjusted for in statistical analyses …”
Section: Methodsmentioning
confidence: 99%
“…It has been well‐demonstrated that filaggrin mutations are population specific, and that common filaggrin mutations in patients with severe AD of European descent are absent in patients of African descent. The fact that ethnic minorities often have a lower socio‐economic status and are more often associated with poor environmental conditions may also have a direct effect on the development of atopic disorders, and this needs to be carefully adjusted for in statistical analyses …”
Section: Methodsmentioning
confidence: 99%
“…17 A subject's proportion of a particular genetic ancestry, which is continuous, might offer a more nuanced method for understanding disparities in outcomes beyond simple dichotomous self-identified racial and ethnic categories, and genetic ancestry analyses are increasingly being used to understand the genetic contribution to disease traits in admixed populations. [18][19][20] For example, African genetic ancestry has been shown to predict lung function and asthma exacerbations among African American subjects better than self-reported race/ethnicity alone. 19,21 To our knowledge, no studies have yet examined the role of genetic ancestry in patients with AD.…”
mentioning
confidence: 99%
“…Спільні генетичні варі-анти, таким чином, мають плейотропний ефект і є об'єктом активного вивчення, оскільки саме вони визначають перспективні напрямки терапії АЗ [9]. На сьогодні відомо більше ніж 300 генів, однону-клеотидні поліморфізми в яких асоційовані із роз-витком атопічних захворювань [14,22].…”
Section: êë³í³÷íà ïåä³àòð³ÿ / Clinical Pediatricsunclassified
“…5 класифікацій, передбачається виділення 4 кате-горій генів, які визначають ризик розвитку ато-пічних захворювань на етапах антигенпрезентації (HLA-Pep-TCR), гіперпродукції IgE (IL-4R, IFN-R1), синтезу та вивільнення медіаторів (LTC4S), та гени, які визначають орган-мішень (ADAM33, IL-13R) [13]. Інші автори виділяють гени, спільні для всіх атопічних захворювань, гени, які кодують білки головного комплексу гістосумісності (MHC), інтерлейкіни (IL), високоафінні компоненти ре-цепторів до IgE та специфічні гени, характерні для певної нозології [9]. Останнім часом підкреслю-ється важливість вивчення асоціацій значущих ге-нів із атопічними хворобами в кожній із популяцій, оскільки відмінності в розподілі алельних варіан-тів не дозволяють впроваджувати результати гене-тичних досліджень в практику охорони здоров'я в усьому світі [9].…”
Section: êë³í³÷íà ïåä³àòð³ÿ / Clinical Pediatricsunclassified
See 1 more Smart Citation